Aircraft noise, overheating and poor air quality in London primary schools' classrooms - Montazami, Azadeh (2012)
Providing a comfortable environment is the fundamental aim in Architecture. Comfortable environment mainly refers to a surrounding atmosphere which is thermally, acoustically, visually, aesthetically, etc. comfortable. Generally, environmental comfort is assessed by environmental factors such as thermal, acoustic and lighting comfort as well as air quality. There is a significant relationship between various environmental factors and students' academic achievements as well as health. Providing all of the environmental factors together is critical as they are interrelated and could conflict if they are considered separately, if the conditions over the life of the building change or relaxed benchmarks are used for design at the first stage. One of the conflicts reviewed in this study, is the conflict between acoustic comfort with thermal comfort and air quality. The hypothesis of this research is that the naturally ventilated schools located in noisy areas (e.g. Heathrow airport) suffer from overheating and poor air quality as well as a high level of background noise during summer periods, due to the lack of ventilation. The main means of ventilation in majority of the UK schools is window. In noisy areas, the classrooms' occupants (i.e. pupils, teachers) often tend to shut windows especially during silent (such as exams and readings) and lecturing activities to reduce the aircraft noise, which varies from 57dB-75dB according to their distances to Heathrow airport. On an average, as a result of closing windows, the aircraft noise drops by 15dB (depending on the type of windows) which makes the inside noise to be around 42dB-60dB. This is still higher than the 35dB which is the acceptable limit for background noise for primary school classrooms as recommended by Building Bulletin 93. The results of the study show that closing of windows does not reduce the high level of background noise to the recommended level, but it also has two negative impacts on classrooms' environments. Firstly it increases the potential for classrooms to experience overheating and secondly it causes poor air quality due to the lack of sufficient ventilation in the building. Through objective and subjective surveys, classrooms' indoor temperatures, air quality and background noise levels were evaluated and it was learnt that those schools located in the vicinity of Heathrow Airport are more likely to experience overheating and poor air quality. This has a negative impact on students' achievements. In addition, one of the reasons for the lack of environmental comfort is the use of relaxed benchmarks. It is shown in this study that overheating and air quality benchmarks which are proposed by 'Department for Education and Skills' in Building Bulletin 101 and used to design and refurbish the UK schools, are relaxed benchmarks in comparison with the others which are proposed by different organisations and researchers. The overall findings of this thesis have been developed to draw the attention of school designers' to the current and future potential conflicts between the comfort factors in schools' classrooms. To prevent failure, extra care should be taken to select a suitable ventilation strategy for providing both air quality and thermal comfort during summer for the schools located under the flights paths. For such schools, it would be beneficial that the solar gain and internal gain are controlled and heavy thermal mass materials are used for their construction. Such strategies would counterweigh the lack of ventilation in protecting the classrooms from overheating. It is also suggested that a further section is incorporated to the comfort section of the school design assessment tools to evaluate the current and future potential conflict between comfort issues in the schools' buildings. In addition, air quality and summer thermal comfort guidelines incorporated to BB 101 are recommended to be revised (similar to the acoustic section of this guideline which was revised to stringent benchmarks for background noise level and reverberation time and included in BB93).